Art That Transforms: Bullying Prevention Through Student Poster Works in Elementary School - Setiawan, Anang; Yani, Muhammad Turhan; Setyowati, Rr Nanik (IKIP Widya Darma Surabaya, 2023)
Objective: Educational programs are planned to maximize the means to reach educational goals, but recently, bullying among elementary school students has become a pressing issue in education. Bullying is an unethical act that is carried out continuously. The causes vary, ranging from family environment, community, school, and social media viewing. Method: This study used the literature review method to investigate the impact of bullying prevention through art in the form of student poster works. Data was collected using the PRISMA method, with data analysis using qualitative research. This study aims to determine the effectiveness of posters in preventing bullying in elementary schools from various literatures. Results: The results show that using art as a poster in elementary schools can effectively strengthen students' awareness of bullying issues. The poster works created by students allow them to express their feelings and responsibilities regarding this issue and provide a platform for them to understand the negative impact of bullying on individuals and the school environment. Novelty: This research underscores the importance of arts integration in the primary education curriculum to combat bullying effectively.